IMPLEMENTASI KEBIJAKAN KAWASAN TANPA ROKOK DI RUMAH SAKIT UMUM DAERAH WANGAYA KOTA DENPASAR - Urbaningrum, Zura Anis; Yudartha, I Putu Dharmanu; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2020)
ABSTRACT Denpasar City regulates non-smoking areas through Denpasar City Regulation Number 7 of 2013. Wangaya Regional General Hospital is a location designated as a no-smoking area. This study uses descriptive qualitativei methods withi data collection techniques in the form ofoobservation, interviewssandddocumentation. This study uses an implementationi model according to Van Meter and Van Horn through 6 indicators that influence the application of public policies, namely policy standardssand objectives, resources, communicationbbetween organizations, organizational characteristics, social, economic and politicall conditions and theeattitude of implementers. The results of this study are the implementationnof no-smoking areas in the Wangaya general hospital has not run optimally due toolack of human resources and socialization activities that are not comprehensive so that people do not understand the restrictions on smoking bans in hospitals and unregulated use of electric cigarettes has become an obstacle in enforcing regional regulations on non-smokinggareas. Keywords: Policy Implementation, nonnsmoking.area, Wangaya Hospital